Mood profiles of amateur triathletes: Implications for mental health and performance - Parsons-Smith, Renée L.; Barkase, Sherry; Lovell, Geoff P.; Vleck, Veronica; Terry, Peter C. (Frontiers in Psychology, 2022)
Moods have been shown to be predictive of athletic performance and a reflection of mental health status. We investigated pre-performance moods in the sport of triathlon, with a focus on relationships among mood, performance, and mental health indicators. Participants were 592 age-group triathletes (also referred to as recreational or amateur triathletes) who completed the Brunel Mood Scale pre-race and recorded their time goal for the race. Participants’ finish times were obtained via their race number through the official race websites. Our sample reported a mean mood profile that approximated an “iceberg profile” except for above average Tension scores. Females reported higher Tension scores than males (p < .001), and those in the 18‒25 yr. and 26‒35 yr. age bands reported higher Tension scores than those in the 46‒55 yr. age band (p < .008). Mood scores did not predict triathlon performance, assessed by finish time as a percentage of time goal, despite the performance measure being objective, self-referenced, and individualized. Mean mood scores showed significant deviation from established normative scores for all subscales, with Tension and Vigor scores at the 55th and 54th percentile respectively and Depression, Anger, Fatigue, and Confusion scores between the 42nd and 46th percentile. Using k-means cluster analysis, six distinct mood profiles were identified among the triathletes, the distribution of which approximated the general population, except for a low prevalence of very negative profiles. Mean scores for Depression and Anger were exceptionally low and only 1.5% of triathletes, compared to the normal prevalence of ~5%, reported an “inverse Everest” profile, which is associated with elevated risk of psychopathology. We conclude that these results suggest an association between triathlon participation and psychological well-being. Results may inform future investigations of mood responses among triathletes and assist the work of applied practitioners working in the sport.